Educating young consumers through debate on global issues: a summer experience with the United Nations Foundation - Hamm, Molly M. (My University, 2015)
The People’s Speak’s foremost initiative in 2007-2008 was the Global Debates competition. In a partnership with the National Forensic League (NFL) and the International Debate Education Association (IDEA), the Global Debates competition provided two debate topics (one in October, the other in March) centered around climate change. High school students and debate teams from domestic and international schools had the opportunity to create public debates using the provided debate topics. In addition to hosting a public debate, schools were challenged to win a trip to the United Nations for the Youth Leadership Summit on climate change by completing a variety of activities including sending photos from the event, writing blog entries about the debate topic, receiving press, and inviting elected officials to the debate. The Youth Leadership Summit was the culminating event of all the hard work that these high school students had put in through the 2007-2008 year. The summit was held July 17-19 in New York City with over 180 students from 9 countries in attendance. Planning and execution of the Youth Leadership Summit was the main focus of my summer internship with The People Speak.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Hamm, M. M. (2008). Educating young consumers through debate on global issues: a summer experience with the United Nations Foundation. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Climatic changes; Environmental education; Debates and debating--Competitions; Leadership--Congresses; United Nations Foundation--Study and teaching (Internship); Reports; Reports